2018
DOI: 10.3390/ijerph15112602
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Ulcerative Colitis in Patients with Periodontal Disease: A Nationwide Population-Based Cohort Study

Abstract: Both periodontal disease (PD) and inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are important diseases of the alimentary tract. Microbiome and immune-mediated inflammatory processes play important roles in these diseases. An association between PD and IBD may exist. This study investigated the risk of IBD in patients with PD. This study used data from the National Health Insurance Research Database of Taiwan from 1996 to 2013. A total of 27,041 patients with PD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…In contrast, there is little evidence regarding the risk of developing IBD in patients with periodontitis. A Taiwanese cohort study reported a 1.56-fold significantly higher risk of UC, but not CD, in 27000 patients with periodontal diseases, including acute periodontitis, chronic periodontitis, and gingivitis[ 34 ], which is comparable with our results in a nationwide study of 1 million subjects with chronic periodontitis. Our study has the strength of demonstrating the impacts of chronic periodontitis, which may reflect the dynamics of chronic inflammatory conditions and lifestyle factors, such as cigarette smoking, on the pathogenesis of IBD.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, there is little evidence regarding the risk of developing IBD in patients with periodontitis. A Taiwanese cohort study reported a 1.56-fold significantly higher risk of UC, but not CD, in 27000 patients with periodontal diseases, including acute periodontitis, chronic periodontitis, and gingivitis[ 34 ], which is comparable with our results in a nationwide study of 1 million subjects with chronic periodontitis. Our study has the strength of demonstrating the impacts of chronic periodontitis, which may reflect the dynamics of chronic inflammatory conditions and lifestyle factors, such as cigarette smoking, on the pathogenesis of IBD.…”
Section: Discussionsupporting
confidence: 89%
“…While a sustained release could be considered ideal, it is important to note that the kinetic of release is a parameter that is also influenced by the percentage of chitosan [82]. Drugs, such as statins [83], doxycycline [84], or other antibiotics/antiseptics such as tetracyclines, have been incorporated in such devices [85,86,87].…”
Section: Resultsmentioning
confidence: 99%
“…Oral administration of Porphyromonas gingivalis (strain W83) in C57BL/6 mice had significant effects on the composition of gut microbes and on the barrier function of the intestines, and led to the spread of intestinal bacteria to the liver. Recently, two cohort studies conducted in Taiwan revealed an increased risk of periodontitis in CD patients compared with that in non‐CD subjects [hazard ratio (HR) = 1.36, 95% CI: 1.25–1.48], and the risk of UC was also increased in patients with periodontitis compared with that in controls (HR = 1.56, 95% CI: 1.13–2.15), indicating a two‐way interaction between IBD and periodontitis. However, the specific mechanisms of pathogenesis and interactions between the conditions remain unclear.…”
Section: Discussionmentioning
confidence: 99%